Glucanase activity produced by rhizospheric Streptomyces tritolerans ARJ 32 and Streptomyces collinus ARJ 38 and the analysis of their encoding genes - DEMMA ZILBA BUDIMAN; WIDYA ESTI PURWANINGTYAS; JEPRI AGUNG PRIYANTO; IVAN PERMANA PUTRA; ABDJAD ASIH NAWANGSIH; ARIS TRI WAHYUDI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Budiman DZ, Purwaningtyas WE, Priyanto JA, Putra IP, Nawangsih AA, Wahyudi AT. 2023. Glucanase activity produced by rhizospheric Streptomyces tritolerans ARJ 32 and Streptomyces collinus ARJ 38 and the analysis of their encoding genes. Biodiversitas 24: 5831-5837. The enzyme ?-1,3-glucanase is capable of breaking down the glucan components in the cell walls of phytopathogenic fungi. Streptomyces spp. isolated from the maize rhizosphere, are believed to produce enzymes with glucanolytic activity, making them promising candidates for use as a biological control agent against these fungi. This work aims to quantitatively analyze the enzymatic activity of glucanase in Streptomyces tritolerans ARJ 32 and Streptomyces collinus ARJ 38 and identify their encoding genes (bglS) and the three-dimensional modeling of their protein structures. The dinitrosalicylic acid (DNS) method quantitively assays the glucanase enzyme. The TA-Cloning of the bglS gene was performed using pGEM-T Easy Plasmid Vector, and the three-dimensional protein structure was constructed using the I-TASSER program. According to the findings, both Streptomyces isolates exhibited glucanolytic activity. The glucanase enzyme activities of S. tritolerans ARJ 32 and S. collinus ARJ 38 peaked at eight days of incubation, with values of 31.116 U/mg and 41.599 U/mg, respectively. The partial bglS gene was present in both Streptomyces and identified as endo-?-1,3-glucanase from the glycoside hydrolase family 16 (GH 16). The deduced partial amino acid sequences were aligned and showed some highly conserved residue in the catalytic domain of GH 16. The three-dimensional structural model built from the partial bglS amino acid sequences displayed high-quality parameters and overlapped with the protein model of partial endo-?-1,3-glucanase from Nocardiopsis sp. F96 (2HYK). These preliminary results suggest that the two Streptomyces isolates had the potential to be used as glucanase enzyme producers.